Security of the Baltic States: Effectiveness of the EU Common Security and Defence Policy and Influence of the Ukrainian Crisis - Gladysh, Marianna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
The paper explores the reasons behind and the development of the EU Common Security and Defence Policy (CSDP), and its advantages and disadvantages that have emerged in the process of its formation and implementation. The transformation of the CSDP according to the Lisbon Treaty and the prospects of its operation in Europe are highlighted. Special attention is paid to the issues of improving the CSDP in the context of new threats to regional and global security. The place and role of the Baltic states in the CSDP are analysed. The position of the Baltic states in NATO, based on greater confidence in the institutions of NATO and close cooperation with the United States is considered. The basic threats and security challenges for the Baltic states nowadays are defined, including possible aggression from Russia, which is broadcast through the mainstream media as a reaction to the idea of protecting the Russian-speaking population of the Baltic states and the establishment of “geopolitical balance through their return to the Russian sphere of influence.”

W artykule przeanalizowane zostały przyczyny i rozwój unijnej Wspólnej Polityki Bezpieczeństwa i Obrony (WPBiO), jej zalety i wady ujawnione w procesie tworzenia i wdrażania. Szczegółowo przedstawiono transformację WPBiO zgodnie z Traktatem Lizbońskim oraz perspektywy jej działania w Europie. Szczególną uwagę zwrócono na kwestie poprawy efektywności funkcjonowania WPBiO w kontekście nowych zagrożeń dla bezpieczeństwa regionalnego i globalnego. Dodatkowo przeanalizowano miejsce i rolę państw bałtyckich w WPBiO. Do podstawowych zagrożeń i wyzwań bezpieczeństwa przed jakimi stoją zaliczane są przede wszystkim ewentualna agresja ze strony Rosji, która opiera się na idei ochrony ludności rosyjskojęzycznej w państwach bałtyckich oraz ustanowieniu „równowagi geopolitycznej poprzez ich powrót do rosyjskiej strefy wpływów”.
Bezpieczeństwo państw bałtyckich: skuteczność Wspólnej Polityki Bezpieczeństwa i Oobrony i wpływu „kryzysu ukraińskiego”
Keywords: Common Security and Defence Policy (CSDP); the EU; European security; Ukraine; Russian Federation; Baltic states; Wspólna Polityka Bezpieczeństwa i Obrony (WPBiO); UE; bezpieczeństwo europejskie; państwa bałtyckie; Ukraina; Rosja